A comparative study of vocational education and occupational safety and health training in China and the UK. Issue 2 (3rd April 2018) - Nie, Baisheng; Huang, Xin; Xue, Fei; Chen, Jiang; Liu, Xiaobing; Meng, Yangyang; Huang, Jinxin
Abstract : In order to enhance Chinese workers' occupational safety awareness, it is essential to learn from developed countries' experiences. This article investigates thoroughly occupational safety and health (OSH) in China and the UK; moreover, the article performs a comparison of Chinese and British OSH training-related laws, regulations and education system. The following conclusions are drawn: China's work safety continues to improve, but there is still a large gap compared with the UK. In China a relatively complete vocational education and training (VET) system has been established. However, there exist some defects in OSH. In the UK, the employer will not only pay attention to employees' physiological health, but also to their mental health. The UK's VET is characterized by classification and grading management, which helps integrate OSH into the whole education system. China can learn from the UK in the development of policies, VET and OSH training.